1984
DOI: 10.4141/cjas84-262
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Fate of Leucine in Muscle and Adipose Tissue of Sheep

Abstract: Leucine (0.1 mM) was preferentially incorporated into proteins rather than being oxidized in intact external intercostal muscle fiber bundles from sheep. At higher leucine concentrations, oxidation became more important. Leucine metabolism in muscle was reduced by starvation. Leucine was not a significant precursor of fatty acids in sheep adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Leucine is also used for protein synthesis and for lipid incorporation, although at a lower rate. Our results are in agreement with previous results that demonstrated that leucine is a deficient precursor of fatty acids and sterols in adipose tissue of sheep, rats, and mice [Feller and Feist, ; Rosenthal et al, ; Wijayasinghe et al, ; Vernon et al, ]. Although, further studies are needed to evaluate whether hormones or other metabolites are capable of modifying BCAA metabolic fate in primary adipocytes, our work establishes a basis for these further studies.…”
Section: Discussionsupporting
confidence: 93%
“…Leucine is also used for protein synthesis and for lipid incorporation, although at a lower rate. Our results are in agreement with previous results that demonstrated that leucine is a deficient precursor of fatty acids and sterols in adipose tissue of sheep, rats, and mice [Feller and Feist, ; Rosenthal et al, ; Wijayasinghe et al, ; Vernon et al, ]. Although, further studies are needed to evaluate whether hormones or other metabolites are capable of modifying BCAA metabolic fate in primary adipocytes, our work establishes a basis for these further studies.…”
Section: Discussionsupporting
confidence: 93%